Peningkatan Regulasi Diri Melalui Journaling: Studi Pada Remaja Perempuan - Muh. Nur Haq I. S. Mannesa; Imam Dedikasi Malik Nur (LPPM Universitas Abdurrab, 2025)
This study aims to evaluate the effectiveness of journaling in improving self-regulation in adolescent girls. The research subjects consisted of 14 adolescent girls aged 19-21 years old who were selected by simple randomization. The study used a pre-experiment design with one-group pretest-posttest. The instrument used was the Self-Regulation Questionnaire (SRQ) adapted by Puspawardani (2019). The journaling intervention was conducted for 14 days with the journaling book guide, followed by pre-test and post-test measurements. Data analysis using paired samples t-test showed significant improvement in participants' self-regulation (p < 0.001), with a mean pre-test score of 42.36 which increased to 57.86 in the post-test (Cohen's d = 2.34). These results indicate that journaling is effective in improving emotion management, impulse control, and future planning. This study recommends journaling as a practical method for self-development and emotion regulation in adolescent girls.